Unraveling age-related impairment of the neuromuscular system: exploring biomechanical and neurophysiological perspectives - Nùñez-Lisboa, M.; Valero-Breton, M.; Dewolf, A. H. (Frontiers in Physiology, 2023)
With extended life expectancy, the quality of life of elders is a priority. Loss of mobility, increased morbidity and risks of falls have dramatic individual and societal impacts. Here we consider the age-related modifications of gait, from a biomechanical and neurophysiological perspective. Among the many factors of frailty involved (e.g. metabolic, hormonal, immunological), loss of muscle strength and neurodegenerative changes inducing slower muscle contraction may play a key role. We highlight that the impact of the multifactorial age-related changes in the neuromuscular systems results in common features of gait in the immature gait of infants and older adults. Besides, we also consider the reversibility of age-related neuromuscular deterioration by, on the one hand, exercise training, and the other hand, novel techniques such as direct spinal stimulation (tsDCS).